Global coverage of interventions to prevent and manage drug-related harms among people who inject drugs: a systematic review. Issue 5 (May 2023) - Colledge-Frisby, Samantha; Ottaviano, Sophie; Webb, Paige; Grebely, Jason; Wheeler, Alice; Cunningham, Evan B; Hajarizadeh, Behzad; Leung, Janni; Peacock, Amy; Vickerman, Peter; Farrell, Michael; Dore, Gregory J; et al.
Summary: Background: Harm reduction and treatment programmes are essential for reducing harms for people who inject drugs (PWID). We aimed to update estimates from a 2017 review of global coverage of needle and syringe exchange programmes (NSPs), opioid agonist treatment (OAT), and other harm reduction services that target PWID (eg, take-home naloxone [THN] programmes, supervised consumption facilities, and drug checking services). Methods: We did a systematic review of available evidence from peer-reviewed and grey literature databases for studies published between Jan 1, 2017, and May 31, 2022. Programmatic data were collected on the availability of services, the number of sites, people accessing services, and equipment distributed in countries where there is evidence of injecting drug use. National estimates of coverage of OAT (ie, number of people accessing OAT per 100 PWID) and NSPs (ie, number of needles and syringes distributed per PWID per year) were generated where available using the most recent data. Regional and global estimates were derived and compared with WHO indicators. The study was registered with PROSPERO (CRD42020173974). Findings: We included 195 studies and found there were 90 countries implementing OAT (75% of the PWID population) and 94 countries implementing NSPs (88% of the global PWID population). Only five countries (2% of the global PWID population) are providing high coverage of both services. Far fewer countries were implementing THN programmes (n=43), supervised consumption facilities (n=17), and drug checking services (n=26), with nine countries implementing all five services. Globally, we estimated there were 18 (95% uncertainty interval [UI] 12–27) people accessing OAT per 100 PWID, and 35 (95% UI 24–52) needles and syringes being distributed per person who injects drugs per year. More countries reported high (OAT 24; NSPs 10), moderate (OAT 8; NSPs 15), and low (OAT 38; NSPs 47) coverage of services compared with the previous review. Interpretation: Global coverage of OAT and NSPs has increased modestly in the past 5 years but remains low for most countries. Programmatic data on other key harm reduction interventions are scarce. Funding: Australian National Health and Medical Research Council.